CancerCare: A reliable and secured self-supervising and interactive system using deep learning - Khisa, Pushpakali; Hossain, Arisha; Raihana, Anika; Khan, Alisha; Tonu, Tamanna Sultana (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.